Parole in liberta futuriste - Caruso, Luciano (Firenze : L'Indiano, 1977)
Marinetti, Filippo Tommaso ; Cangiullo, Francesco ; Carrà, Carlo ; Cerati, Morpurgo e ; Gigli), Jamar 14 (Piero ; Fillia ; Depero, Fortunato ; Gerbino, Giovanni ; Benedetta ; Masnata, Pino ; Scurto, Ignazio ; Cervelli, Fernando ; Ginna, Arnaldo ; d'Albisola, Tullio ; Gallina, Luigi
Italiaans
boek